Identification of Prospective Surface Water Available Zones with Multi Criteria Decision Approach in Kushkarani River Basin of Eastern India - , Shahana Khatun, Swades Pal (Archives of Current Research International, 2016)
Present paper mainly intends to find out suitable sites for surface water harvesting in Kushkarani river basin a tributary of Mayurakshi river of Eastern India. For this multiparametric potential surface water availability model and SCS CN based runoff depth models have been prepared in soft ware environments. Both unweighted and weighted linear combination methods are used for compositing the selected parameters. Results show that 14.18% of a total basin area (172 sq. km.) characterised by very high surface water potential is mainly concentrated in the confluence segment of the river followed by high potential zone covering 22.47% area. Unweighted composting model based estimation shows that very high and high surface water potential zone cover 8.22% and 21.95% of basin area, but areal extent in these two classes is little bit lower than the results obtained from weighted composting model. Field based discharge measurement validates the surface water potential zones. Similarly, Discharge availability in the rivers of different potential zones are also indicating very accordant result and validating the surface water runoff models. SCS CN based runoff depth model represents that 9.32% area covers very high runoff depth (657 mm. to 693 mm.). Calculated Relative error value and Nash-Sutcliffe efficiency values are respectively 53.65% and 0. 6782 which represent that runoff model is not highly optimum but it is within the range of acceptability. Correlation coefficient value between monsoon runoff depth and surface water potentiality (r=0.6453) is high and it is significant at 0.01 level of significance which does indicate both the models are highlighting result in same direction. For validating these models with field based discharge data, it is noticed that discharge data strongly controls surface water availability (R2=0.962) and runoff depth (R2=0.970). From the models it is proved that specifically, confluence segment and very proximate riparian low land of the rivers is selected as suitable sites for surface water harvesting.